Young people from refugee backgrounds as a resource for disaster risk reduction. (December 2015) - Marlowe, Jay; Bogen, Rachel
Abstract: Young people from refugee backgrounds represent an important resource for disaster risk reduction within their respective communities. This paper presents a qualitative study with young people from refugee backgrounds and their experiences of the 2010–2011 Canterbury earthquakes in New Zealand. The interviews and focus group discussions with these participants highlighted their capacities as cultural brokers and mediators, as they ensured that their respective communities had access to disaster related information that was translated and interpreted. Thus, young people from refugee backgrounds represent a bridge that can connect people from their ethnic communities to key disaster information through their linguistic capital, digital literacies and social networks to support the recovery process. As part of the recovery effort, these young people also emphasised the need for more inclusive social and recreational spaces to be able to meaningfully participate in the (re)imagining of the city. This paper discusses how young people from refugee backgrounds can offer leadership within their communities and can play integral roles in disaster risk reduction.